Biofertilizer Business Development Strategy Based on Fermented Water Waste: A Triple Layer Business Model Canvas Approach - Jannah, Wardatul; Ria, Vina Yunita; Ubaidillah, Ubaidillah; Maharani, Anjar; Sihotang, Woulden Hood; Ibanah, Indah; Soetriono, Soetriono; Kuntadi, Ebban Bagus; Damascena, Cindera Rosa (JSEP (Journal of Social and Agricultural Economics), 2024)
Indonesia is a country that has high potential in the agricultural sector. However, the use of fertilizers that are not environmentally friendly, the continuous application of chemicals, and inappropriate land management and cultivation systems will increase land degradation and cause losses for future generations. The "Jakatik" product is an innovative solution for the bio-fertilizer business for eternal lucky mushrooms with probiotics from leri water waste, fruit, and vegetables, an effort to utilize and improve the economy of biological waste materials. The aim of this research is to determine mapping using the Triple Layer Business Model Canvas (TLBMC) approach and to determine sustainable decision-making using the Plus Minus Implication Analysis (PMIA) method approach. The research method uses descriptive and analytical methods. The research results show 1) The results of the business model mapping based on TLBMC in the economic layer describe all the elements and are strengthened, the environmental layer cannot describe the End of life element, because the packaging is not environmentally friendly. Meanwhile, the social layer cannot describe the elements of social culture and social impact because there is no special responsibility given to society and there is no negative social impact. 2) Decision making based on PMIA (Plus Minus Implication Analysis) analysis, the economic layer produces the highest score of 114, so it is necessary to strengthen the business model in customer segment elements by increasing promotions. The environmental layer produces a low score of 91, so it is necessary to develop a business model in the form of adjustments to production quantities according to marketing targets and urge users to apply immediately. Meanwhile, the social layer produces 112 values, so it is necessary to strengthen the business model, especially at the end-user element, by including rules of use.